A Deixis Analysis of Song Lyrics of Shania Yan “Nothing’s Gonna Change My Love for You” - Nendah Sari Indriani; Ayang Winda Sri Widianingsih (JEPAL (Journal of English Pedagogy and Applied Linguistics), 2023)
The purpose of this study was to investigate the types of deixis used in Shania Yan song lyrics, to determine the type and dominant types used, and to describe the semantic meaning of the deixis. Song lyrics are associated with deixis because they express the singer's or song writer's feelings or emotions, which are represented by some human thoughts, ideas, and opinions. The descriptive qualitative research design was used for this study. The information was obtained from the song lyric 'Nothing's gonna change my love for you'  by Shania Yan. The findings show that there are four types of deixis which appears with 133 data. Personal deixis appears 80 data with a percentage of 60%. Next is discourse deixis appears 31 data with a percentage of 23%, temporal deixis appears 17 data with a percentage of 13% and spatial deixis appears 5 data with a percentage of 4%. Thus, the most dominant type of deixis that appears in this song is person deixis, it is because the singer tells on their life, feelings and emotions.